Characterising the complexity of medication safety using a human factors approach: an observational study in two intensive care units. Issue 1 (19th September 2013) - Carayon, Pascale; Wetterneck, Tosha B; Cartmill, Randi; Blosky, Mary Ann; Brown, Roger; Kim, Robert; Kukreja, Sandeep; Johnson, Mark; Paris, Bonnie; Wood, Kenneth E; Walker, James
Abstract : Objective: To examine medication safety in two intensive care units (ICU), and to assess the complexity of medication errors and adverse drug events (ADE) in ICUs across the stages of the medication-management process. Methods: Four trained nurse data collectors gathered data on medication errors and ADEs between October 2006 and March 2007. Patient care documents (eg, medication order sheets, notes) and incident reports were used to identify medication errors and ADEs in a 24-bed adult medical/surgical ICU and an 18-bed cardiac ICU in a tertiary care, community teaching hospital. In this cross-sectional study, a total of 630 consecutive ICU patient admissions were assessed to produce data on the number, rates and types of potential and preventable ADEs across stages of the medication-management process. Results: An average of 2.9 preventable or potential ADEs occurred in each admission, that is, 0.4 events per patient-day. Preventable or potential ADEs occurred in 2.6% of the medication orders. The rate of potential ADEs per 1000 patient-days was 276, whereas the rate of preventable ADEs per 1000 patient-days was 9.2. Most medication errors occur at the ordering (32%) and administration stages (39%). In 16–24% of potential and preventable ADEs, clusters of errors occurred either as a sequence of errors (eg, delay in medication dispensing leading to delay in medication administration) or grouped errors (eg, route and frequency errors in the order for a medication). Many of the sequences led to administration errors that were caused by errors earlier in the medication-management process. Conclusions: Understanding the complexity of the vulnerabilities of the medication-management process is important to devise solutions to improve patient safety. Electronic health record technology with computerised physician order entry may be one step necessary to improve medication safety in ICUs. Solutions that target multiple stages of the medication-management process are necessary to address sequential errors.